2014
DOI: 10.1038/cdd.2014.62
|View full text |Cite
|
Sign up to set email alerts
|

PKCλ/ι signaling promotes triple-negative breast cancer growth and metastasis

Abstract: Triple-negative breast cancer (TNBC) is a distinct breast cancer subtype defined by the absence of estrogen receptor (ER), progesterone receptor (PR) and epidermal growth factor receptor 2 (HER2/neu), and the patients with TNBC are often diagnosed with higher rates of recurrence and metastasis. Because of the absence of ER, PR and HER2/neu expressions, TNBC patients are insensitive to HER2-directed and endocrine therapies available for breast cancer treatment. Here, we report that expression of atypical protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 56 publications
3
50
0
Order By: Relevance
“…Luminal‐type breast cancer patients express estrogen, progesterone and HER2 receptors on the cancer cells and respond to endocrine and HER2 targeted therapies, respectively . Basal‐type breast cancer is the most aggressive phenotype, in which cancer cells lack expression of these receptors (triple negative) and therefore patients do not respond to endocrine, chemo‐ and radiation therapies . A recent report suggests that triple negative breast cancers (TNBCs) develop chemoresistance within a few years of initial treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Luminal‐type breast cancer patients express estrogen, progesterone and HER2 receptors on the cancer cells and respond to endocrine and HER2 targeted therapies, respectively . Basal‐type breast cancer is the most aggressive phenotype, in which cancer cells lack expression of these receptors (triple negative) and therefore patients do not respond to endocrine, chemo‐ and radiation therapies . A recent report suggests that triple negative breast cancers (TNBCs) develop chemoresistance within a few years of initial treatment .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study specifically demonstrated that PRKCI signaling promotes TNBC cell growth and metastasis through NF-κB pathway which could be regulated by TGFβ and IL1β25. We previously reported a new oncogenic role for RNA binding protein FXR1 linking to PRKCI and ECT2 in NSCLC9.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, none of our 3q 19 genes overlaps with known gene signatures tested in this study, arguing a lack of efficacy of using these known gene signatures as prognostic factors in TNBC patients. Although the exact role of these 19 genes in breast cancer metastasis is unclear, 12 genes including FXR1 have been studied functionally or mechanistically in human cancers including lung and breast (Supplemental Table 21)919202122232425. For instance, PIK3CA is the most well-studied oncogene among our 3q gene signature due to its high mutation rate in human cancer, especially in breast cancer23.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that the aPKC iota/lambda and zeta isoforms may have distinct functions in regulating proliferation based on their requirement in different cell types. For example, the iota/lambda isoform promotes the growth and metastasis of triple-negative breast cancers, a subtype defined by the absence of estrogen receptor, progesterone receptor and epidermal growth factor receptor 2 21 . However, the zeta isoform is required for the mitogen induced growth of squamous cell carcinomas of the head and neck 22 .…”
Section: Apkc Regulates Differentiation In Diverse Physiological Contmentioning
confidence: 99%